The INFLUENCE OF CORPORATE GOVERNANCE, CORPORATE SOCIAL RESPONSIBILITY AND CARBON EMISSION DISCLOSURE ON THE SUSTAINABILITY : OF COMPANIES LISTED ON THE SRI-KEHATI INDEX - Neng Kurnia Asih; Eddy Winarso (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2024)
After COVID-19 hit at the beginning of 2019, it hit the economy in various countries, especially Indonesia, which saw a decline in profits for the affected companies. Apart from that, lessons can be learned that implementing good governance, social responsibility (CSR) and reducing carbon emissions are important things to implement for company sustainability. The sample for this research was selected using a purposive sampling method, obtaining 9 companies listed on the Sri-Kehati Index that met the criteria with a total of 45 data. The research uses multiple linear regression analysis for the influence of corporate governance, corporate social responsibility and carbon emission disclosure on company sustainability. The research results show that corporate governance and corporate social responsibility have no effect on company sustainability. However, carbon emission disclosure has a positive effect on company sustainability. This research can be used as a reference by companies as input for caring about social and environmental issues and for future researchers as an additional reference in conducting research.